2004
DOI: 10.1038/nature02641
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the α1–β subunit interaction of voltage-gated Ca2+ channels

Abstract: High-voltage-activated Ca2+ channels are essential for diverse biological processes. They are composed of four or five subunits, including alpha1, alpha2-delta, beta and gamma (ref. 1). Their expression and function are critically dependent on the beta-subunit, which transports alpha1 to the surface membrane and regulates diverse channel properties. It is believed that the beta-subunit interacts with alpha1 primarily through the beta-interaction domain (BID), which binds directly to the alpha-interaction domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
332
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(344 citation statements)
references
References 29 publications
6
332
2
4
Order By: Relevance
“…All Ca V β subunits share a conserved domain structure with three variable regions separated by conserved SH3-like and GK-like domains [77]. The Ca V α interaction site is located within the GK domain of all Ca V β subunits and supports high affinity (low nanomolar) association with a conserved domain (termed the AID) of the α-subunits [77][78][79]. As first shown with Rem [71], and subsequently with the remainder of the RGK GTPases [18], deletion mapping studies have located the RGK binding domain to a region within the larger GK domain of Ca V β.…”
Section: Rgk Inhibition Of Voltage-dependent Ca 2+ Channelsmentioning
confidence: 99%
“…All Ca V β subunits share a conserved domain structure with three variable regions separated by conserved SH3-like and GK-like domains [77]. The Ca V α interaction site is located within the GK domain of all Ca V β subunits and supports high affinity (low nanomolar) association with a conserved domain (termed the AID) of the α-subunits [77][78][79]. As first shown with Rem [71], and subsequently with the remainder of the RGK GTPases [18], deletion mapping studies have located the RGK binding domain to a region within the larger GK domain of Ca V β.…”
Section: Rgk Inhibition Of Voltage-dependent Ca 2+ Channelsmentioning
confidence: 99%
“…Together with work in rat hippocampal neurons (46), this suggested that membrane-associated guanylate kinase scaffolding proteins with PDZ, SH3, and guanylate kinase domains such as CASK are likely involved in targeting and stabilizing Ca v 2 calcium channels to synaptic contacts. It is interesting to note that calcium channel ␤ subunits also contain membrane-associated guanylate kinase-like SH3 and guanylate kinase domains (33)(34)(35), raising the possibility that secondary interactions of ␤ subunits with scaffolding proteins may aid in stabilizing and anchoring of LCa v 2 calcium channels in synaptic terminals.…”
Section: Lymnaea Neurons Express a Ca V ␤ Subunit-a Full-lengthmentioning
confidence: 99%
“…1, A and C). Residues in the guanylate kinase domain contribute to form a deep, hydrophobic groove for high affinity binding of high voltage-activated calcium channels (33,35), which are highly conserved residues among invertebrate and mammalian ␤ subunits (Fig. 1A, black residues).…”
Section: Lymnaea Neurons Express a Ca V ␤ Subunit-a Full-lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional structure of the Ca V b subunits has been determined at high resolution by X-ray crystallography (Fig. 3B) (Chen et al 2004;Van Petegem et al 2004). These subunits contain conserved SH3 and guanylate kinase domains like the MAGUK family of scaffolding proteins.…”
Section: Three-dimensional Structure Of Ca 2þ Channelsmentioning
confidence: 99%